AgIncentives policy indicators to support scenario analysis for assessing better outcomes for poverty, food security and climate change mitigation: IPSR Innovation Profile - Vos, Rob; Martin, Will; Thurlow, James; Mamun, Abdullah; Cantillo, Marco V. Sánchez; Gautam, Madhur; Gruère, Guillaume P.; De Salvo, Carmine Paolo (CGIAR System Organization, 2024)
An integrated framework of global and country Agri-Food Market and Policy Analysis Models (AMPAM) is implemented to assess the potential for and trade-offs associated with scaling interventions and innovations that create jobs, boost incomes, and reduce environmental footprints along food value chains. A key component of AMPAM is the consistent and comparable set of indicators of degrees of policy support to agriculture and food sectors by type of support, food commodities, and countries. This set of policy indicators has been prepared in collaboration with the AgIncentives Consortium (FAO-IFPRI-IDB-OECD-World Bank). Together with the agrifood market database and the AMPAM modeling framework, the policy indicator dataset will be a critical ingredient for the scenario analysis the Initiative will undertake to support decision-makers in assessing the full potential, scalability, market opportunities, priorities for, and trade-offs associated with incentive schemes, and investments and innovations.